The correlation between sleep quality and fatigue in students at 'Aisyiyah University Yogyakarta - Taghsya Dhaneswara Patya; Rokhmah, Noor Ariyani; Masitoh, Rohayati (Universitas 'Aisyiyah Yogyakarta, 2024)
Students have many responsibilities and demands that must be completed to meet their learning load and must meet academic standards. This makes students sleep-deprived so that it can cause fatigue. Fatigue is an obstacle felt by students when studying because students feel that there is a decrease in energy when carrying out activities during the day and cause symptoms of drowsiness. This study aims to determine the correlation between sleep quality and fatigue in students at 'Aisyiyah University Yogyakarta. The method carried out in this study is a correlational quantitative with a cross-sectional design in students at 'Aisyiyah University Yogyakarta who used the Pittsburgh Sleep Quality Index (PSQI) questionnaire for sleep quality and the Swedish Occupational Fatigue Inventory (SOFI) questionnaire for fatigue. The sampling technique used proportionate stratified random sampling with a total of 375 student respondents. The research was analyzed using the Kendall Tau test. The results showed that the majority of students experienced poor sleep quality as many as 284 students (75.7%) and moderate fatigue of 301 students (80.3%). The results of the bivariate analysis test obtained the result of p=0.000 (p<0.05) stating that there was a correlation between sleep quality and fatigue in students at the University of 'Aisyiyah Yogyakarta. It can be concluded that there is a correlation between sleep quality and fatigue in students of 'Aisyiyah University Yogyakarta.